Karakteristik Manajemen Organisasi Santri dalam Pembentukan Jiwa Kepemimpinan di Pondok Pesantren Al-Kautsar Pajo NTB - Suci Kurniasihanto, Arief; Nurrahmaniah, Nurrahmaniah (LP2M, Institut Agama Islam Qamarul Huda, 2025)
This study aims to analyze the characteristics of student organizational management at the Al-Kautsar Pajo Islamic Boarding School in West Nusa Tenggara (NTB) and its contribution to the formation of student leadership. This descriptive qualitative study involved observation, in-depth interviews, and documentation. The results indicate that student organizational management fosters the values ​​of discipline, responsibility, and collective leadership through a deliberation-based management structure and routine activities. These findings broaden the study of Islamic boarding school leadership by emphasizing the integration of modern management systems and Islamic values.